Forgery of a Will with Due Regard to Civil and Criminal Law - Muda Sipayung, Iskandar; Hasanah, Uswatun (International Asia Of Law and Money Laundering, 2024)
This study aims to determine first, how the inheritance system in the book- Civil Law (Civil Code). Secondly, to find out how the forgery of a will in view of criminal law. This type of research is Library research and the research approach used is juridical normative approach. The data sources of this research are primary, secondary and tertiary data sources through legislation, books, journals and rulings. Data analysis is used by way of identification and classification of existing data and organize it systematically. The results of this study indicate that in the inheritance system according to the Civil Code there are two ways to obtain an inheritance, namely first, obtaining an inheritance based on the provisions of the act- law and second, obtain an inheritance based on testament. The existence of restrictions on certain parties that result in the abolition of the right to inherit which is one of the reasons for committing the crime of forgery of wills.